Macrophage Differentiation and Polarization Regulate the Release of the Immune Checkpoint Protein V-Domain Ig Suppressor of T Cell Activation - Noubissi Nzeteu, Gaetan Aime; Schlichtner, Stephanie; David, Sulamith; Ruppenstein, Aylin; Fasler-Kan, Elizaveta; Raap, Ulrike; Sumbayev, Vadim V.; Gibbs, Bernhard F.; Meyer, N. Helge (Frontiers in Immunology, 2022)
Recently, the V-domain immunoglobulin suppressor of T-cell activation (VISTA) was identified as a negative immune checkpoint regulator (NCR) that is mainly expressed in hematopoietic cells. Preclinical studies have shown that VISTA blockade results in impeded tumor growth and improved survival. Nevertheless, little is known about the physiological role of VISTA expression in macrophages. This study focused on the differential expression of VISTA in human monocytes and macrophages in order to elucidate a putative role of VISTA regulation upon macrophage polarization and activation. We observed that human peripheral monocytes constitutively release soluble VISTA, which was mediated by proteolytic cleavage via matrix metalloproteinase 9 (MMP-9). However, monocyte stimulation with cytokines that induce macrophage differentiation, such as granulocyte-macrophage colony–stimulating (GM-CSF) and macrophage colony-stimulating factor (M-CSF), substantially reduced soluble VISTA release. VISTA release was further affected by various pro- and anti-inflammatory stimuli that lead to macrophage polarization, where activated M1 macrophages generally released more VISTA than M2 macrophages. Additionally, we observed that stimulation of activated macrophages with the toll-like receptor 4 ligand lipopolysaccharide (LPS) led to a further decrease of soluble VISTA release. Moreover, we found that soluble VISTA impairs T cell cytotoxic activity but did not induce their programmed death. Our results suggest that VISTA is constantly produced and released in the peripheral blood where it may contribute to peripheral tolerance.